Appointment of Heirs as Funeral Prayer Leaders in the Bukittinggi Community: An Analysis of Designation from the Perspectives of Customary and Islamic Law - Wardi, Utama; Ikhwan, Ikhwan; Busyro, Busyro (Hakamain: Journal of Sharia and Law Studies, 2024)
This research delves deeper into the longstanding practice of appointing heirs as leaders of funeral prayers within the cultural tapestry of the Kurai community in Bukittinggi. It endeavors to unravel the socio-cultural fabric that deems heirs as appropriate custodians of this sacred ritual, exploring the historical evolution and societal roles entrenched in traditional funeral ceremonies. Methodologically, this research utilizes a qualitative approach through in-depth interviews with local community leaders to gain a direct understanding of the appointment of heirs as leaders of funeral prayers. This approach is enriched by scholarly discourse on highly relevant legal and religious issues, enhancing the analysis with theoretical perspectives and comparative viewpoints. By synthesizing these interdisciplinary approaches, the research aspires to unravel the intricate nuances and underscore the profound significance of heirs assuming the mantle of funeral prayer leadership in the Kurai community in Bukittinggi. The findings from this study are anticipated to yield nuanced insights into the intricate interplay between indigenous traditions and Islamic principles within the realm of religious practices in the Kurai community. This scholarly inquiry aims to foster novel perspectives and enrich ongoing dialogues on how local adaptations harmonize with and enrich Islamic values in everyday life. In contribution to existing literature, this research offers a deeper understanding of the socio-cultural dynamics that influence the appointment of heirs as funeral prayer leaders. It also provides a nuanced exploration of the legal and religious implications of this practice, thereby contributing to broader discussions on the adaptation of Islamic norms in local contexts.